YASHIL IQTISODIYOT SHAROITIDA BARQAROR RIVOJLANISHNI TA’MINLASHNING IQTISODIY VA INSTITUTSIONAL OMILLARI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the economic and institutional foundations of sustainable development in the context of the green economy. The role of state policy in environmental protection, efficient use of resources, development of renewable energy, and ecological safety is highlighted. Based on the example of Uzbekistan, priority directions for the transition to a green economy, investment policy, and innovative technologies are discussed. The author proposes recommendations for improving institutional reforms, digital technologies, and environmental management systems in developing the green economy.